Sacrum w drodze. Moskwa-Pietuszki Wieniedikta Jerofiejewa i Pulp Fiction Quentina Taranino w kluczu montażowego czytania - Waligórska-Olejniczak, Beata (Adam Mickiewicz University Press, 2013)
The aim of this monograph is the attempt of reading the poem Moscow-Petushki by Venedikt Erofeev and the film Pulp Fiction by Quentin Tarantino using the comparative approach, in which we go beyond the range of factual relationships, historical influences or similarities functioning in the structure of the presented world. The purpose of the book is to see both works of art from the angle of the montage theory of Sergei Eisenstein – the outstanding and highly regarded Russian director and film philosopher – which means studying cultural phenomena in their mutual intertextual relationships. The book focuses on the interpretation of the selected Tarantino’s and Erofeev’s texts of culture, in which the subject of the city, the search for the concept of the body at the end of 20th century and the problem of addictions constitute the dominant thematic issues. The monograph also offers the insight into the nature of the phenomenon of postmodernism and treats Eisenstein’s philosophy as the specific type of anticipation of postmodern tendencies in cinematography.
Keywords: Tarantino, Jerofiejew, Moskwa-Pietuszki, Pulp Fiction, postmodernizm, alkohol, używki, miasto, ciało